Designing effective digital learning environments - Gegenfurtner, Andreas; Kollar, Ingo (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Bringing together the research of leading international scholars in the field of digital learning, Designing Effective Digital Learning Environments discusses cutting edge advancements in digital technology and presents an evidence-informed summary of best practice for effective design principles and implementation within educational settings. Readers will benefit from a synthesis of research evidence from previous meta-analyses on how to design digital environments that support learning, motivation and collaboration. Divided into eight thematic parts, chapters unpack: An introduction to digital learning environments Learning with multimedia, with particular emphasis on digital reading and GeoGebra software Videos for learning, including dynamic visualisations, instructional videos, and eye movement modelling examples Simulated realities, pedagogical agents and immersive virtual reality Game-based and sensor-based learning in digital environments Digital learning in social contexts, including a discussion of social media, CSCL and audience response systems Designing digital classrooms with approaches such as flipped classrooms and synchronous online learning A concluding section discussing the efficacy and design of digital learning environments This edited volume is an essential read for any scholar, researcher, PhD or Masters student working in the field of digital learning"--
Keywords: Web-based instruction -- Design; Instructional systems -- Design; Educational innovations; EDUCATION / Educational Psychology; EDUCATION / Computers & Technology